Quantifying air pollution vulnerability and its distributional consequences: Some perspectives from Delhi - Gupta, Shivani; Das, Sukanya; Murty, M. N. (Indian Society of Ecological Economics, 2019)
This paper estimates Vulnerability Index of air pollution in Delhi taking into account exposure, susceptibility and coping capacity of households. A general health production function model and a vulnerability assessment framework are used for this purpose. Data was collected through a survey of sample households located in close vicinity to 10 air pollution monitoring stations in Delhi. The estimated vulnerability index is used to show the effect of household exposure to air pollution. The vulnerability index takes into consideration sample households' socio-economic status, demographic profile and other characteristics. Result showed that households of lower socio-economic status were the most vulnerable to air pollution and its consequences.